Animated Video Based on Tri Hita Karana Fourth Grade Energy Sources Learning Topic - Pranata, I Made Gunawan Wahyu Adi; Suartama, I Kadek (Universitas Pendidikan Ganesha, 2023)
The conventional learning process makes students feel bored and affects their knowledge competency. This research aims to create an animated video based on Tri Hita Karana on natural science energy sources. This research is development research by applying the ADDIE development model. The subjects of this research were student responses, 2 media experts, 2 materials experts, and 2 practitioners. This research uses a questionnaire or questionnaire data collection method to measure validity using a rating scale instrument. Data analysis methods and techniques in this research use qualitative and quantitative descriptive analysis. The validity test results of the animated video based on Tri Hita Karana on the topic of energy sources were obtained, the validity of which was tested with an average score of 4.69 for media experts, 4.68 for material experts, 4.69 for practitioner experts and student test results or average student responses average 5. In conclusion, the Tri Hita Karana-based animated video on learning energy sources is very good quality and suitable for fourth-grade science subjects in elementary schools. This research implies that it can facilitate students' understanding of energy source materials using animated video media.